(Re)Producing Nature in Pyrmont and Ultimo. (3rd July 2014) - TROY, LAURENCE
Abstract Urban political ecology (UPE), as articulated by Heynen et al., is premised on the refusal to ontologically separate nature and society. The urban becomes representative of an unbounded process of 'urbanisation', a complex interplay between ecological, political, and economic processes that produce historically and geographically contingent outcomes. Importantly, it advances a historical conception of nature, and problems in and of nature, that necessarily encompasses the socio‐economic conditions of its production. This paper presents research into the formation of urban sustainability policy in Australia that draws on the theoretical insights offered by the UPE approach. Using one of Australia's largest urban regeneration projects as a focus, Pyrmont and Ultimo in Sydney, this paper discusses how the politics and economics of urban change and development framed possibilities of how urban environmental problems were firstly understood and, secondly, how they could be addressed. In doing so, this foreclosed alternative visions of urban policy that do not align with hegemonic forms of socio‐economic regulation.